High-Performing Li-Ion Battery with “Two Cathodes in One” of Sulfur and LiFePO4 by Strategies of Mitigation of Polysulfide Shuttling - Garay-Marin, Juan David; Quiroga-Gonzalez, Enrique; Garza-Tovar, Lorena Leticia; Reuter, Florian; Kensy, Christian; Althues, Holger; Kaskel, Stefan (Batteries & Supercaps, 2021)
This work reports on further development of the concept “two cathodes in one” for lithium-ion batteries. The cathodes are composed of LiFePO4 (high power) and sulfur (high gravimetric capacity), allowing high discharging rates as well as high gravimetric capacities, which are especially attractive for numerous existing applications. In this study, different strategies have been tested to reduce polysulfide shuttling in batteries with these cathodes, greatly improving their performance. Batteries which were assembled with electrolyte mixtures of tetramethylsulfone and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TMS/TTE) show significantly better performance than with the typical electrolyte composition used for Li−S batteries. Moreover, various carbons with different pore size distributions in the C/S composite were mixed with LiFePO4 in an electrode reaching high discharge capacities (72 % of the theorical composite capacity) and stable Coulombic efficiency of 99 %. As a result, an improved active material utilization is observed, confirming its possible application as a commercial battery cathode.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon; composite cathodes; electrochemistry; Li-ion batteries; Li−S batteries